Students’ Perception of Using Humor in Teaching English Class at SMAN 2 Tilatang Kamang - Yana, Rahma; Syahrul, Syahrul (FOSTER: Journal of English Language Teaching, 2023)
There were several student problems that the writer found at SMAN 2 Tilatang Kamang. First, Some students agree on using humor in the classroom, but some students disagree on using humor in the classroom. Second, Some students said that using humor in teaching English is necessary to make the atmosphere pleasant. Using humor in teaching helped them to understand the material quickly and made them enjoy the learning. Last, Some students said that the use of humor in learning English is good as long as they don't laugh too much in class because it will take up a lot of time in the learning process and cause the learning process to be not optimal. So, some students do not understand the material. This research aims to determine students' perceptions of using humor in teaching English classes. The researcher wants to determine whether students' perceptions are positive or negative. The instrument of this research used a quantitative approach with a descriptive form. The population was the Eleventh Grade at SMAN 2 Tilatang Kamang in 2020/2021, with 75 students. The researcher used the total sampling technique because the population was less than 100 students. The result of this research was taken by taking the average score of 6 types of humor in learning English, namely learning Caricature Humor (78,07%), Short Stories/Anecdotes Humor (78,53%), Special Humor (74,13%), and Unplanned Humor, Performance, Pantomime, and Gestures (73,12%). It was found that male and female students have positive perceptions of humor in teaching English. Female students had slightly better perceptions than male students (75,74%>73,81%). Thus, the result of the research showed that students supported the use of humor in teaching English class.